Bottom up synthesis of boron-doped graphene for stable intermediate temperature fuel cell electrodes. (October 2017) - Tennyson, Wesley D.; Tian, Mengkun; Papandrew, Alexander B.; Rouleau, Christopher M.; Puretzky, Alexander A.; Sneed, Brian T.; More, Karren L.; Veith, Gabriel M.; Duscher, Gerd; Zawodzinski, Thomas A.; Geohegan, David B.
Abstract: The high surface area and electrical conductivity of few-layered graphene would make it an ideal catalyst support and electrode in fuel cells apart from its susceptibility to oxidative corrosion. Here we report the single-step, bottom-up synthesis of oxidation-resistant boron-doped graphene and show its increased stability in the aggressive electrochemical environment of intermediate temperature solid acid fuel cells (SAFCs). Boron was shown to alter the growth mode of single walled carbon nanohorns by laser vaporization to produce high yields of thin (<20 layer) boron-doped (2–3 at.%) crystalline flakes of turbostratic graphene (B-GLF). Alternatively, adding partial pressures of hydrogen less effectively shifted the growth mode of SWCNHs toward planar, turbostratic graphene-like flakes (GLFs). Thermogravimetric analysis indicates that boron-doping enhances the oxidation resistance of few-layer GLFs by >140 °C, with large fractions of multilayered B-GLFs surviving 10 °C/min ramps to 1000 °C. These B-GLFs provided a stable Pt catalyst support and electrode over 40 h operation in SAFCs with cesium dihydrogen phosphate electrolyte operating at 250 °C, as opposed to undoped GLFs or SWCNHs which were nearly completely consumed. The facile synthesis and oxidation-resistant properties of boron-doped GLF appear promising for graphene applications in oxidizing environments. Graphical abstract: